The Speed of Neural Visual Motion Perception and Processing Determines the Visuomotor Reaction Time of Young Elite Table Tennis Athletes - Hülsdünker, Thorben; Ostermann, Martin; Mierau, Andreas (Frontiers in Behavioral Neuroscience, 2019)
Purpose: Recent research in adult badminton athletes has shown the visuomotor reaction time is strongly dependent on the speed of visual signal perception and processing in the brain’s visual motion system. However, it remains unclear if this relation can be confirmed for other visuomotor demanding disciplines as well as different age groups. This study aimed to validate previous findings in international elite youth table tennis players to shed light on the generalizability of neural performance determinants across different visuomotor demanding sports and age groups. Methods: 37 young elite international table tennis players (18 male, 19 female, mean age: 13.5 years) from 23 nations participated in this study. Participants performed a visuomotor reaction task in response to visual motion stimuli presented at two different motion velocity conditions. Visuomotor performance was evaluated by measuring the electromyographic (EMG) onset as well as the visuomotor reaction time (VMRT). In addition, a 64-channel electroencephalography (EEG) system was used to investigate the stimulus and response-locked event-related potentials in the brain’s visual motion sensitive area MT as well as the pre- and supplementary motor cortex indicating the speed of cortical visual and motor information processing, respectively. Correlation and multiple regression analyses identified the neural processes determining visuomotor performance. Results: The VMRT (232 vs. 258 ms, P < 0.001, d=-2.33) and EMG onset (181 vs. 206 ms, P < 0.001, d=-2.14) were accelerated in the fast motion velocity condition which was accompanied by an earlier stimulus-locked N2 (187 vs. 193 ms, P < 0.001, d=-0.80) and later response-locked N2-r (17 vs. -0.1 ms, P < 0.001, d=1.04). The N2 and N2-r latencies were correlated with EMG onset and VMRT in both velocity conditions and explained between 80-90% of the variance in visuomotor reaction speed. Neural processes in BA6 did not differ between stimulus velocity conditions and did not contribute to the regression model. Conclusion: The results validate our previous findings and support the importance of neural visual processes for the visuomotor reaction speed across different visuomotor demanding sports and age groups. This suggests the visual system might be a promising target for specific visual diagnostics and training interventions.